An Iterative Algorithm for Solving Fixed Point Problems and Quasimonotone Variational Inequalities. (8th February 2022) - Yin, Tzu-Chien; Wu, Yan-Kuen; Wen, Ching-Feng
Abstract : In this paper, we survey a common problem of the fixed point problem and the quasimonotone variational inequality problem in Hilbert spaces. We suggest an iterative algorithm for finding a common element of the solution of a quasimonotone variational inequality and the fixed point of a pseudocontractive operator. Convergence theorems are shown under some mild conditions. Several corollaries are also obtained.